Performance analysis of covert wireless communication based on beam forming with noise uncertainty - Yuda LIN; Liang JIN; You ZHOU; Yangming LOU (Tongxin xuebao)
In order to establish covert wireless communication in Rayleigh fading environment with noise uncertainty,a scheme of downlink covert wireless communication based on complex Gaussian random coding and beam forming was adopted,and more importantly,the performance of covert wireless communication was analysed.Firstly,the covert probability of communication was analyzed by using the hypothesis test theory.Secondly,the optimal detection threshold of the illegal detection party was given and proved,and the closed expressions of the average covert probability,connection interruption probability and covert throughput of the system were further obtained.Finally,by jointly designing the transmission power and target covert rate,the optimal goal of the maximum covert throughput of the system was achieved,and the corresponding algorithm based on step search was given.The simulation results show that the beam forming technology could provide some gain for covert wireless communication.Compared with the ideal case in which the legitimate receiver is not affected by the noise uncertainty,the covert throughput in non-ideal case is significantly reduced and almost not affected by the basic noise level of the environment.